Design and Implementation of Super Capacitor Based DVR Circuit for Power Quality Enhancement - Dr. Sunil Kumar Gupta, Dr. Javed Khan Bhutto (International Journal of Modern Agriculture, 2020)
Power quality complications are the sensitive issue in a power network. Two power quality issues are frequently arise in distribution structure, which are swells and voltage sag. Power quality issues affect the sensitive load. To diminish the voltage swell and sag the Dynamic Voltage Restorer (DVR) device is used. Super-Capacitors based DVR system is suggested for mitigate the swell and voltage sag. It has the ideal characteristics like low energy density and high power for compensate the voltage sag and swell. In this proposed super capacitor based DVR provides excessive power in a short interval of time and it is work as an energy storage. The DC-DC converter is used for integrated DVR with super capacitor. The temporary voltage sag and voltage swell is also compensated by this technique.